Implementasi Kebijakan Satu Peta dalam Rangka Penyelesaian Tumpang Tindih Pemanfaatan Ruang Kabupaten Kotawaringin Timur - Wahyuningsih, Sri (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
This study analyzes the problem of overlapping spatial utilization in Kotawaringin Timur Regency, Central Kalimantan, which is an essential challenge in realizing the vision of Golden Indonesia 2045. The study aims to identify the causes of spatial overlap and develop strategies to resolve it. Then, using a qualitative approach, this study collected data through interviews, observations, and a review of related documents. The study results revealed that the leading causes of spatial overlap are the limited quality of human resources who master geospatial information, low budget capacity, and weaknesses in regulations in the licensing mechanism. In 2023, the mismatch between licensing and land rights reached 50.89% of the area of 1,556,540 hectares, and although it decreased to 38.24% in 2024, this problem is still significant. Differences in map standards between Kotawaringin Timur Regency and Central Kalimantan Province and the lack of transparency regarding information regarding spatial utilization triggered this conflict. This study recommends increasing human resource capacity in managing geospatial information, adequate budget allocation, and better regulatory arrangements. Joint commitment from the central, provincial, and regional governments is also needed to resolve this issue, ensure planned spatial utilization, and support future sustainable development.